A cláusula escalonada na sucessão hereditária de empresas familiares - Carvalho, Maria Helena Campos de (2019)
The present paper deals with the appropriate ways of solving conflicts, seeking to identify a more adequate methodology for cases of hereditary succession, in the hypothesis of the role of assets to contemplate quotas or actions of family companies. An analysis is made of the characteristics and forms of family business, highlighting the importance of small and medium-sized enterprises and the inadequacy of the Judiciary to deal with inventories that aim to share inheritance, but which end up, in the cases of companies family members, to cause them to be extinguished, either by delay in the proceedings or by the absence of elements that allow the judge to make a specific and non-detrimentary decision both to the companies and to the person of the heirs. This theme is justified by the fact that the peculiarity of family business encompasses both personal aspects and family conflicts as well as the patrimonial aspect. In a context in which 90% of Brazilian companies are of family origin, a closer analysis of the situation is imperative. In order to do so, a number of cases have been studied, used as examples, and the possibility of resolving this impasse with the least possible cost to the parties involved has been sought in appropriate forms of conflict resolution, especially in phased clause, but, at the same time, the satisfaction sought in judicial proceedings